2009
DOI: 10.2202/1548-923x.1639
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes in a Traditional versus Accelerated Nursing Curriculum

Abstract: In this descriptive study, graduates of a traditional baccalaureate nursing program were compared with graduates of an accelerated baccalaureate program at the same university between 1991 and 2006. A survey was sent to a random sample of two groups: traditional baccalaureate graduates and graduates of the accelerated program who had previous degrees in another major and completed the nursing curriculum in a shorter time frame than the traditional students, resulting in a total sample of 73 graduates. Outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…It remains unknown whether the acceptance of the need to perform compliance as a student nurse will result in eventual conformity, or if the position claimed by participants will provide them with avenues to exercise their critical thinking skills and in so doing achieve the future roles and the job satisfaction they privately desire. It is suggested that it is these qualities that could be a more accurate reflection of the components of graduateness than those rehearsed in the literature (Youssef & Goodrich 1996, Bently 2006, Aktan et al 2009). However, additional comparison-based studies with students from undergraduate courses would be required to confirm this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains unknown whether the acceptance of the need to perform compliance as a student nurse will result in eventual conformity, or if the position claimed by participants will provide them with avenues to exercise their critical thinking skills and in so doing achieve the future roles and the job satisfaction they privately desire. It is suggested that it is these qualities that could be a more accurate reflection of the components of graduateness than those rehearsed in the literature (Youssef & Goodrich 1996, Bently 2006, Aktan et al 2009). However, additional comparison-based studies with students from undergraduate courses would be required to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…These relate to motivation and commitment (Meachin & Webb 1996) alongside the specific study skills and thinking styles that they bring with them as a result of prior education and experience (Carter & Peile 2007). However, it is evident that these findings are either based on the opinion of those who have been involved in educating students belonging to these groups, or on speculative views which attempt to explain quantitative comparative data documenting their success (Youssef & Goodrich 1996, Bently 2006, Aktan et al 2009).…”
Section: Graduateness and Graduate Entry Nursingmentioning
confidence: 99%
“…In addition, students who have a bachelor's degree in another discipline can receive , 2001, 2002, 2003, 2004, 2005, 2006a, 2007, 2008. a a baccalaureate in nursing in an accelerated second-degree or "fast track" program. These programs of condensed nursing content, although not a new idea, have become increasingly more condensed and can be completed in 15 to 18 months (down from 2 years required in the 1990s) and have rapidly expanded (Aktan et al, 2009). Accelerated programs have had a resurgence due to the current nurse shortage.…”
Section: Entry Into Nursing Practicementioning
confidence: 99%
“…Students in these programs are generally younger than students enrolled in associate degree programs and on average 5 to 8 years older than traditional baccalaureate nursing students (Aktan et al, 2009;Brewer et al, 2009). Studies comparing students in traditional baccalaureate programs to those in the accelerated programs have determined few differences.…”
Section: Accelerated Bsn Programsmentioning
confidence: 99%
See 1 more Smart Citation